The first transcriptome dataset of roselle (Hibiscus sabdariffa L.) calyces during maturation - Hamzah, Nur Atheeqah; Seok, Christina Yien Yong; Nallappan, Meenakshii (Elsevier, 2022)
Roselle (Hibiscus sabdariffa L.) is recognized for its phytochemical compounds such as anthocyanins, which possess pharmacological potentials in the treatments of hypertension, diabetes, cancer, hyperlipidaemia and hyperglycaemia. The calyx is the most commercially valuable part of the roselle and usually harvested at maturation. However, genetic study to understand the transcriptome changes in the calyx during maturation has yet to be explored. In this study, we sequenced the transcriptomes of roselle calyces at maturation stages III and IV using Illumina NextSeq 500 platform. These are the two most critical maturation stages in roselle, as these stages are often associated with the quality of the calyx. Over 200 million good quality paired-end reads were generated and de novo assembled into a reference transcriptome consisting of 221,334 transcripts with N50 score of 491bp. Among these transcripts, 92,974 transcripts (42%) were successfully annotated. The total number of significantly differentially expressed genes (DEGs) and the top five most significantly regulated genes in each of the maturation stage were presented. Twenty-one genes implicated in the biosynthesis of anthocyanins and their relative expressions in the calyx tissues at the two maturation stages were reported. Two secondary metabolites biosynthesis pathways that attained a relatively higher number of DEG mappings compared to other pathways were also reported. The findings from this work provide novel insights to better understand the transcriptional changes in roselle during calyx maturation, and the data made available here is intended for continued genetic study on roselle.